Oviposition Preference of Callosobruchus maculatus (F.) to Common Pulses and Potentiality of Triflumuron as their Protectant (Journal of Bio-Science, 2009)
Seeds of black grams, lentils, Bengal grams and green peas were soaked separately in aqueous solutions of Triflumuron at doses of 0.0 (control), 0.5, 1.0, 1.5 and 2.0 ppm. Three day -old adults of Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) were allowed to oviposit on air-dried, treated or untreated pulses of each type and dose in âno-choice' and âfree-choice' tests. Maximum oviposition occurred in Bengal grams (61.00? 0.25) and green peas (33.67? 0.54) in âno-choice' and âfree-choice' tests, respectively. The beetles avoided egg laying on lentils. Maximum egg-hatching occurred on black grams (>90%) in both tests. Minimum developmental time was required in the Bengal grams (30? 0.5 days in âno-choice' test and 31.33? 1.23 days in âfree-choice' test). No adults emerged from green peas, while 54.79% and 86.15% emergence were recorded from untreated black grams in âno-choice' and âfree-choice' tests, respectively. Triflumuron reduced egg-laying significantly in green peas, where hatchability also reduced significantly to 35.99% at 2 ppm in âno-choice' test. Percentage of hatching decreased in all pulses with the increasing doses of triflumuron. No adults emerged from the treated green peas in any test, and at 2 ppm the adult emergence declined to < 50% in all pulses. Implications of these results are further discussed. Â Key words: Callosobruchus maculatus, Triflumuron, seed protectant, fecundity, hatchability, developmental period, adult emergence Â  doi: 10.3329/jbs.v15i0.2207 J. bio-sci. 15: 83-88, 2007